Aetiology and associations of halitosis: A systematic review. (5th March 2022) - Memon, Maaz Anwer; Memon, Hifza Anwer; Muhammad, Faizan E; Fahad, Shehzad; Siddiqui, Amna; Lee, Ka Yiu; Tahir, Muhammad Junaid; Yousaf, Zohaib
Abstract: Halitosis is a term that refers to an unpleasant or foul odour originating from the oral cavity that can be caused by either intra‐oral or extra‐oral factors. Despite the fact that halitosis has multifactorial aetiology, intra‐oral factors play a significant role in the majority of cases. This systematic review assesses halitosis's intra‐oral and extra‐oral associations. An electronic search through MEDLINE (PubMed), Google Scholar and the Wiley Online Library was conducted to identify relevant manuscripts. A keywords‐based search was performed, using the terms 'halitosis', 'bad‐breath', and 'oral malodour causes and aetiology'. Articles published from January 2014 to December 2020 were included. We selected studies evaluating the intra‐oral and extra‐oral factors that induce oral malodour, as well as the factors associated with systemic diseases. Eighty to ninety percent of halitosis is caused by intra‐oral factors, with coated tongue, periodontal diseases and poor oral hygiene practices being the principal factors. Ten to twenty percent of halitosis is induced by extra‐oral factors associated with systemic diseases. Multiple factors can cause halitosis, but most of the aetiology is intra‐oral. Increased medical awareness is needed to determine the actual pathophysiological process of oral malodour in otherwise healthy individuals.